Group Counseling with Humanistic Approach to Improve Santri SelfAdjustment - Sunarti, Titi; Y.R, Yustiana; Nurhudaya, Nurhudaya (International Conference on Elementary Education, 2020)
The inability of students to adapt to the environment of the boarding school causes problems. Adjustment is one of the important aspects in an individual's effort to master unpleasant feelings or pressures due to impulse needs, efforts to maintain a balance between meeting the needs and demands of the environment and efforts to harmonize the relationship of individuals with reality. The humanistic counseling approach aims to make students experience their existence authentically by becoming aware of its existence. Authentic existence is fully aware of the present situation, choosing how to live in the present, and being responsible for his choices, developing potential, and being conscious to open up and act according to his abilities. The method used in the study of library research methods The results of the study concluded that a conceptual humanistic approach can be used to improve the adjustment of students in Islamic boarding schools so that students are able to realize their existence in Islamic boarding schools, choose to live in Islamic boarding schools and be able to take responsibility for their choices